2019
DOI: 10.3390/su11102934
|View full text |Cite
|
Sign up to set email alerts
|

Conventionalization of Organic Farms in Germany: An Empirical Investigation Based on a Composite Indicator Approach

Abstract: The term “conventionalization” of organic agriculture was created to depict the controversially discussed phenomenon that organic agriculture departs from the core organic principles on which it is based. We present an empirical, index-based approach to investigate developments of organic farming practices towards conventionalization. An index of conventionalization can be used as a monitoring tool to support policymakers to further develop agricultural regulations. We calculate composite indicators for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Combined with the linear aggregation technique, PCA has been widely used in the past research on designing composite indices, as it produces weightings describing the statistical importance of each of the sub-indicators [19]. Examples of successful application of this method can be found in [22,23]. A comprehensive review of other weighting and aggregation techniques can be further found in [19].…”
Section: Composite Index For Comprehensive Assessment Of Power System...mentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with the linear aggregation technique, PCA has been widely used in the past research on designing composite indices, as it produces weightings describing the statistical importance of each of the sub-indicators [19]. Examples of successful application of this method can be found in [22,23]. A comprehensive review of other weighting and aggregation techniques can be further found in [19].…”
Section: Composite Index For Comprehensive Assessment Of Power System...mentioning
confidence: 99%
“…In such an orthogonal rotation method, the axes remain orthogonal during rotation. The varimax rotation can optimise the loadings so that each components represents only a few variables, and each of the original variables is associated with a small number of PCs, facilitating the interpretation, and hence varimax rotation is chosen in the most of the past work [19,23] and in the present paper. In the oblique rotation the new axes could be in any position in the component space, which relaxes the orthogonality constraint so that the simplicity of the interpretation is maximized.…”
Section: ) Principle Component Analysis (Pca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Salvati and Carlucci (2014) proposed a sustainable development indicator for Italy; the research paper combined a wide range of variables and used a statistical tool to determine the composite indicator weights. A similar technique was used by Seidel et al (2019), who developed an indicator to measure organic agriculture. Also, Senna et al (2019) used a statistical tool to develop a water poverty index.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the paradox that the growing success of organic products might be slowed by retailers charging unusually high price premiums [1], hindering the transition towards a more sustainable consumption. Moreover, while the conventionalisation of organic products and offering them in common supermarkets broadens the reach of potential buyers, it risks, at the same time, to violate the sustainable principles of organic production [16]. Retailers follow a profit maximising logic and can leverage their market power.…”
Section: Introductionmentioning
confidence: 99%